PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING PADA SISWA KELAS VIII SMP NEGERI 1 KARANGPLOSO - Yuli Hartanti (Center of Language and Cultural Studies, 2017)
This study reports learning outcomes of social sciences subject through the application of guided discovery learning model. This study was a classroom action research of two cycles. Conducted in SMPN 1 Karangploso Malang in 2015/2016 the study assigned 31studnets of 8th class as the subject. Data were collected through observation, testing, and documentation. This study revealed that learning activities and attainment increased substantially. Scores of pre-test prior to cycles were: above Minimum Mastery Standard (KKM) = 3 (9.6%), 65-74 = 12 (38,71%) , 60-64 =10 (32,26%), and below 60 = 6 (19.35%). Results of cycle I were: mean score 79.41, maximum score 88 and minimum score 64, distributed into: above KKM = 3 (9.67%), 65-74 = 12 (38.71%), 60-64 = 10 (32.26%), and below 60 = 6 (19.35%). Attainment in cycle II were salient showing 29 (93.55%) above KKM and 2 (6.45%) below KKM.